Information on Income, Dividend Policy and the Impact of Inflation on Stock Prices - Yanti, Lia Dama; Aprilyanti, Rina (AKUNTOTEKNOLOGI : JURNAL ILMIAH AKUNTANSI DAN TEKNOLOGI, 2020)
This lookup ambitions to determine the have an impact on of income information, dividend coverage and inflation on inventory prices via the ride of organizations on the LQ45 index of the Indonesian Stock Exchange from 2017 to 2019. Several previous studies on stock fees have proven extraordinary results. Therefore, every other learn about is needed to re-evaluate the stock fee theory. The populace of this study is the LQ45 index of 45 companies. In order to obtain the 3-year commentary period (2017 to 2019) and 57 remark effects of 19 pattern companies, the sampling approach used is a purposeful sampling method. Research facts comes from sample businesses that can be downloaded from the Indonesian Stock Exchange website, and inflation information can be downloaded from the internet site of the Central Bureau of Statistics. The facts analysis techniques used are descriptive statistical analysis and more than one regression analysis. The first facts analysis technique completed is descriptive facts and classical speculation testing. The a couple of regression evaluation continues with speculation testing. The consequences of this study partly show that, as shown via the t-test of zero <0.05, data about profits and dividend coverage will affect the stock price, while the t-test of 0.726 <0.05 indicates that inflation will now not affect the inventory price. The end result of this study is that, at the identical time, earnings information, dividend coverage and inflation will all have an effect on the inventory price, while trying out zero <0.05 (5%).